Synthesis and structural characterization of homochiral homo-oligomers of parent CIS- and trans-furanoid-beta-amino acids - Pandey, Sunil K.; Jogdand, Ganesh F.; Oliveira, Joao C. A.; Mata, Ricardo A.; Rajamohanan, Pattuparambil R.; Ramana, Chepuri V. (Chemistry-A European Journal, 2011)
The synthesis of homochiral homo-oligomers of cis- and trans-3-aminotetrahydrofuran-2-carboxylic acids (parent cis- and trans-furanoid-beta-amino acids, referred to as ``cis-/trans-FAA'') has been carried out to understand their secondary structures and their dependence on the ring heteroatom. The oligomers of two diastereomers have been shown to have a distinct left-handed helicity. The cis-FAA homo-oligomers show a 14-helix structure, in contrast to the homo-oligomers of cis-ACPC, which adopt a sheet like structure. The trans-FAA homo-oligomers were found to adopt a 12-helix structure, the same trend found in trans-ACPC homo-oligomers. With the help of ab initio calculations, the structural features of cis-ACPC and cis-FAA hexamers were compared. We believe that the more compact packing of the cis-FAA hexapeptide should be due to a more favorable interaction between the ring and the backbone amide hydrogen.
Keywords: ab initio calculations; Amino acids; Density functional calculations; Peptides; secondary structures